Reporting of health practitioners by their treating practitioner under Australia's national mandatory reporting law. Issue 1 (18th January 2016) - Bismark, Marie M; Spittal, Matthew J; Morris, Jennifer M; Studdert, David M
Abstract: Objective: To describe the frequency, nature and outcomes of reports about health practitioners made by their treating practitioners under Australia's new mandatory reporting system. Design and setting: Retrospective case file review and analysis of treating practitioner reports received by the Australian Health Practitioner Regulation Agency between 1 November 2011 and 31 January 2013, and of the outcomes of the completed investigations of these reports to November 2014. Main outcome measures: Characteristics of treating practitioners and reported practitioners; nature of the care relationship; grounds for report; regulatory action taken in response to report. Results: Of 846 mandatory reports about medical practitioners, 64 (8%) were by treating practitioners. A minority of reports (14 of 64) were made by a practitioner‐patient's regular care provider; most (50 of 64) arose from an encounter during an acute admission, first assessment or informal corridor consultation. The reported practitioner‐patients were typically being treated for mental illness (28 of 64) or substance misuse (25 of 64). In 80% of reports (50 of 64), reporters described practitioner‐patients who exhibited diminished insight, dishonesty, disregard for patient safety, or an intention to self‐harm. Conclusions: The nature and circumstances of the typical treating practitioner report challenge assumptions expressed in policy debates about the merits of the new mandatory reporting law. Mandatory reports by treating practitioners are rare. The typical report is about substance misuse or mental illness, is made by a doctor who is not the patient's regular care provider, and identifies an impediment to safely managing the risk posed by the practitioner‐patient within the confines of the treating relationship.